Epistemology of the Feelies. Aldous Huxley’s Brave New World and the Dream of Smell Media (Cinéma & Cie. Film and Media Studies Journal, 2023)
The essay analyses from an epistemological point of view the functions of an imaginary medium, the feelies, namely some stereoscopic, tactile, and especially olfactory movies imagined by Aldous Huxley in the futuristic dystopia Brave New World (1932). Its main goal is to comprehend the identity, functions, and objectives of yesterday’s and today’s multisensory media. In this perspective, the essay reconstructs the cultural-historical horizon which produced Huxley’s imaginary entertainment, considering the three polarities which constitute a media dispositive in the perspective of media epistemology, i.e. machinery, representation, and spectator. With regard to the mechanical function of the fictional dispositive, its ability to catch sensory spheres such as smell and touch reflects the contemporary debate on media specificity, a discussion in which Huxley himself participated with a famous 1929 article. In the same way, the fictional feely Three Weeks in a Helicopter appears as a parodic pastiche which bears the marks of various cinematic paradigms of the time: especially early “cinema of attractions”, as well as film genres which communicate directly to the spectator’s unconscious. Finally, focusing on the imaginary spectator’s experience, the essay reconnects feelies to the cultural history of olfaction, a repressed sense whose media conquest coincides with a precise form of colonization of human subjectivity.
Keywords: Imaginary Media; Multisensoriality; Cultural History of Smell; Cinema of Attractions